METODE PENDEKATAN SUFISTIK MENGATASI GANGGUAN KEJIWAAN (STUDI DINAS SOSIAL DI KOTA BANDUNG) - Syihani, Agnia; Yumna, Yumna (Jurnal Dakwah Tabligh, 2022)
Psychiatric disorders are syndromes or patterns of psychological behavior of a person that according to clinically are so meaningful and specifically related to the symptoms of suffering (distress) in important human functions. Sufistic education is a human effort to develop innate potential, both physical and spiritual, by prioritizing the inner, not outside, aspects or by using Sufism materials, where there are aspects related to morality, both moralities with Allah, the Prophet, with fellow human beings as well as for the entire creation of God. This research is a qualitative descriptive study with a background in UPT Halfway House, Bandung City Social Service. This research describes the application of Sufistic approach methods to overcome mental disorders at UPT Halfway House, Bandung City Social Service. Through this approach, although not a significant change, there is a change in good behavior from the client.